Trimetallic Mesoporous AuCuNi Electrocatalysts with Controlled Compositions Using Block Copolymer Micelles as Templates. Issue 12 (15th October 2018) - Nugraha, Asep Sugih; Malgras, Victor; Kim, Jeonghun; Bo, Jiang; Li, Cuiling; Iqbal, Muhammad; Yamauchi, Yusuke; Asahi, Toru
Abstract: Nanostructure engineering is important in the development of metal‐based catalysts to improve material utilization efficiency and catalytic activity. Among the available nanoscale architectures, mesoporous structures have raised much attention due to their large surface area and their highly accessible inner sites for guest species, suitable for a wide range of applications. Gold (Au)‐based materials are promising catalysts thanks to their stability, nontoxicity, and good resistance to poisoning effects. Modifying the composition by introducing inexpensive metals to prepare multicomponent Au‐based catalysts is an effective route to both reduce the cost and improve the catalytic activity. Herein, a polymeric micelle assembly approach to synthesize mesoporous AuCuNi ternary alloy films by electrochemical deposition is reported. This simple method involves the co‐electrodeposition process of Au, Cu, and Ni precursors at fixed applied potential in the presence of polymeric micelles acting as a sacrificial template. The compositional ratio can be easily adjusted to optimize the catalytic performance of the mesoporous AuCuNi films, which show promising results for glucose oxidation and methanol oxidation reactions. It is believed that mesoporous AuCuNi films can be desirable to satisfy the needs for the next generation of multifunctional catalyst. Abstract : A polymeric micelle assembly approach to synthesize mesoporous AuCuNi ternary alloy films is reported. This simple method involves the co‐electrodeposition process of Au, Cu, and Ni precursors at fixed applied potential in the presence of polymeric micelles acting as a sacrificial template. The obtained mesoporous AuCuNi films show promising results for glucose oxidation and methanol oxidation reactions.